Cancer‑associated fibroblasts: a pivotal regulator of tumor microenvironment in the context of radiotherapy - Linhui Zheng; Wenqi Cai; Yuan Ke; Xiaoyan Hu; Chunqian Yang; Runze Zhang; Huachao Wu; Dong Liu; Haijun Yu; Chaoyan Wu (Cell Communication and Signaling)
Abstract Background In the course of tumor treatment, radiation therapy (RT) not only kills cancer cells, but also induces complex biological effects in non-malignant cells around cancer cells. These biological effects such as angiogenesis, changes in stromal composition and immune cell infiltration remodel the tumor microenvironment (TME). As one of the major components of the TME, Cancer‑associated fibroblasts (CAFs) are not only involved in tumorigenesis, progression, recurrence, and metastasis but also regulate the tumor-associated immune microenvironment. CAFs and tumor cells or immune cells have complex intercellular communication in the context of tumor radiation. Main content. Different cellular precursors, spatial location differences, absence of specific markers, and advances in single-cell sequencing technology have gradually made the abundant heterogeneity of CAFs well known. Due to unique radioresistance properties, CAFs can survive under high doses of ionizing radiation. However, radiation can induce phenotypic and functional changes in CAFs and further act on tumor cells and immune cells to promote or inhibit tumor progression. To date, the effect of RT on CAFs and the effect of irradiated CAFs on tumor progression and TME are still not well defined. Conclusion In this review, we review the origin, phenotypic, and functional heterogeneity of CAFs and describe the effects of RT on CAFs, focusing on the mutual crosstalk between CAFs and tumor or immune cells after radiation. We also discuss emerging strategies for targeted CAFs therapy.